Successful treatment of idiopathic retroperitoneal fibrosis with combined immunosuppressive therapy - Obrenčević, Katarina; Petrović, Dejan; Aleksić, Predrag; Petrović, Marijana; Rančić, Nemanja; Jovanović, Dragan; Nikolić, Bojan; Mijušković, Mirjana; Vavić, Neven; Ignjatović, Ljiljana; Maksić, Djoko (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Idiopathic retroperitoneal fibrosis (IRF) is characterized by the fibroinflammatory periaortic tissue that affects the ureters, causing obstructive nephropathy and variable impairment of renal function. The findings strongly suggest an autoimmune etiology. The optimal treatment has not been established. The aim of this study was to analyze a long-term efficacy of combined corticosteroid therapy with mycophenolate mofetil (MMF) in the patients with IRF. Methods. We retrospectively followed 13 patients (8 males and 5 females) with IRF. All patients received corticosteroids and MMF. For the patients with severe renal failure, an initial ureteral decompression was made and prednisone was started orally 0.5 mg/kg with fast tapering. In cases with a mild renal failure corticosteroids were administrated as intravenous methylprednisolone pulses for 3 days, followed by oral prednisone. The dose of MMF was 1000 mg twice a day. MMF was stopped after 18 months and prednisone after 48 months. Results. Systemic symptoms resolved in all patients. Erythrocyte sedimentation (SE) rate declined from the mean of 67.6 to 26.3 mm/h and C-reactive protein (CRP) from the mean of 18.5 to 6.3 mg/L. In 7 out of 8 patients, the ureteral stents were successfully removed 13 weeks on average. Seven patients had 100% of reduction in the periaortic mass, and the average percent reduction was 76.9%. The kidney function improved and remained normal in 6 treated patients. In 4 patients a mild chronic renal failure remained due to afunction of one kidney. Three patients, with a prior chronic renal failure, did not get worse renal function. The disease recurred in 3 patients. There were no treatment side effects noted. Conclusion. Combination of corticosteroids and MMF is a potentially effective treatment in restoring the renal function and reducing the fibrotic tissue in the patients with idiopathic retroperitoneal fibrosis. It could prevent the need for ureteral stenting and surgery. Longer treatment may reduce a possibility of recurrence.
Keywords: retroperitoneal fibrosis; renal insufficiency; autoimmune diseases; adrenal cortex hormones; mycophenolic acid; remission induction; recurrence